2012
DOI: 10.1007/s10853-012-6596-7
|View full text |Cite
|
Sign up to set email alerts
|

High electrochemical activity from hybrid materials of electrospun tungsten oxide nanofibers and carbon black

Abstract: Tungsten oxide (WO 3 ) nanofibers were prepared by oxidizing the electrospun ammonium metatungstate (AMT) and polyvinyl pyrrolidone (PVP) composite fibers. The WO 3 nanofibers with controllable diameters ranging from 80 to 130 nm were obtained by electrospinning different AMT/PVP mixture solutions. Electrochemical activity of the WO 3 nanofibers was measured in 0.5 M sulfuric acid solution. Cyclic voltammetry tests show that the WO 3 nanofibers have electrochemical activity which is closely related to hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…[62][63][64] PVP aids in the colloidal stability and dispersibility of metal oxide particles. Tungsten oxide nanowires with PVP on their surface have been used as photocatalysts and electrocatalysts, [65][66] but the effect of the PVP coating on their activity has not been studied.…”
Section: Resultsmentioning
confidence: 99%
“…[62][63][64] PVP aids in the colloidal stability and dispersibility of metal oxide particles. Tungsten oxide nanowires with PVP on their surface have been used as photocatalysts and electrocatalysts, [65][66] but the effect of the PVP coating on their activity has not been studied.…”
Section: Resultsmentioning
confidence: 99%
“…4c, it is found that the current density of the sample prepared at -0.15 V from the precursor nanofibers calcined at 400°C increases by 10, 7, and 4.7 times than the amorphous precursor nanofibers calcined at 400°C, the crystalline WO 3 nanofibers calcined at 450°C, and the commercial 20 wt% Pt/C catalyst, respectively. The current density obtained for the HWO nanosheets is much higher than other WO 3 nanostructures reported previously [4,8,21,24]. It is believed that the high electrochemical activity of the obtained samples and its changing trend with the applied potential result from the formation and structure changes of the nanosheets.…”
Section: Resultsmentioning
confidence: 57%
“…The electrospinning solutions were prepared by dissolving AMT and PVP in distilled water at the concentrations (w/v) of 6 and 7 %, respectively, where AMT acts as tungsten source for hydrated WO 3 nanosheets and PVP acts as the thickener for electrospinning. The AMT/PVP composite nanofibers were electrospun at 40 kV from the AMT/PVP solution by a conventional setup [24]. Afterwards, the AMT/PVP composite nanofibers were calcined at 400°C for 3 h in a tube furnace in O 2 atmosphere, obtaining the nanofibers with amorphous structure, which were used as the precursor nanofibers for growing the HWO nanosheets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several efforts have been successfully forwarded by various research groups for the efficient preparation of metal oxide nanofibers using electrospinning method. The resulting outcome emphasized the emergence of the electrospinning method to be a compelling technique for the construction of composite and inorganic nanofibers that has various applications including glucose sensor [183][184][185][186][187][188][189][190][191][192][193][194][195][196][197]. Metal oxide nanofibers are prepared in a two-step procedure (i.e., first the organic phase in composite nanofibers is removed via calcinations at high temperature).…”
Section: Metal Oxide Nanofibersmentioning
confidence: 99%